2021
DOI: 10.33765/thate.12.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical investigation of some primitive water sources in district Champawat for potability and preservation of historical aesthetics, Uttarakhand, India

Abstract: The present study deals with the assessment of physicochemical properties of spring water samples collected from the surroundings of Champawat city, Uttarakhand, India. The total of twenty-three parameters were analysed for the study including pH, total dissolved solids (TDS) (mg/L), electrical conductance (EC) (µS/cm), temperature (T) (°C), dissolved oxygen (DO) (mg/L), chloride (Cl- ) (mg/L), and uranium (U) (µg/L). The seasonal variation was also observed in these samples. In the hills, spring water has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The acceptable limit for calcium is 75 mg/l and the accepted limit for magnesium is 30 mg/l. Patni et al (2022) analyzed aquifers of Champawat and their study showed similar results. TH, calcium, and magnesium of their samples were also found under the permissible limits of BIS.…”
Section: Resultssupporting
confidence: 53%
“…The acceptable limit for calcium is 75 mg/l and the accepted limit for magnesium is 30 mg/l. Patni et al (2022) analyzed aquifers of Champawat and their study showed similar results. TH, calcium, and magnesium of their samples were also found under the permissible limits of BIS.…”
Section: Resultssupporting
confidence: 53%
“…Because rivers pass through towns, industrial zones, and agricultural areas, they have long been used for disposal of sewage [6]. According to a World Health Organization (WHO) study, household waste accounts for 80 % of water contamination [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors, such as Patni et al, [7], Lrk et al, [11], and Gupta et al, [15] have reported on the concentration of physiochemical parameters of river water from different places around the world, as well as the pollution status, using the WQI approach. In many areas, there is a serious water deficit and there are problems with the quality of drinking water.…”
Section: Introductionmentioning
confidence: 99%